Modulace toxicity nanočástic železa nulové valence - Pádrová, Karolína; Bajerová, Kristýna; Čejková, Alena (Chemické listy, 2016)
Zero-valent iron nanoparticles (nZVI) are used in remediation technologies. However, their high reactivity is responsible for the nZVI toxicity against autochthonal microorganisms whose participation on a remediation process is important. The aim of this study was to investigate the application of humic substances as a potential protective agent. The activity of nZVI and protective effect of humic substances were studied on gram-positive soil bacteria Rhodococcus erythropolis (CCM 2595). The effectiveness of the humic substances under study was evaluated by the measurement of the cell viability and by tests characterizing the oxidative stress, lipid peroxidation and protein carbonylation.
Keywords: Humic Substances; Spectrophotometry; Oxidative Stress; huminové látky; kovové nanočástice; Rhodococcus; znečištění životního prostředí; mikroskopie elektronová rastrovací; Environmental Pollution; oxidační stres; spektrofotometrie; Metal Nanoparticles; Iron; železo; Microscopy, Electron, Scanning; mikrobiologie životního prostředí; Environmental Microbiology